A negative regulator of metastasis promoting macrophages - Kitamura, Takanori (Journal of Emergency and Critical Care Medicine, 2018)
Breast cancer is one of the leading causes of cancer death in women mainly because the breast cancer cells frequently egress from the primary site and form secondary tumors in the distant organs including the bone and lung (1,2). Since 5-year survival of patients is dramatically reduced once the metastatic tumors are established (2), it is necessary to understand the mechanisms behind the metastatic tumor expansion in order to improve the outcome of breast cancer patients.